High sensitivity pressure measurement using optical fibre sensors mounted on a composite diaphragm - Aime, Laura F. J.; Kissinger, Thomas; James, Stephen W.; Chehura, Edmon; Verzeletti, Alberto; Tatam, Ralph P. (Optical Society of America, 2021)
A pressure sensor specified for aerodynamic applications and based on optical fibre strain sensors mounted on a circular glass fibre reinforced polymer membrane is presented. The use of two fibre optic strain sensing technologies is explored, the novel intrinsic fibre segment interferometry (FSI) approach and fibre Bragg gratings (FBGs), with the use of FSI shown to offer a pressure resolution that is 15 times larger than that achieved using an FBG. A number of design and fabrication issues are considered, including the position of the fibres relative to the neutral axis of the membrane and the influence of the membrane support structure on the thermal and pressure sensitivities of the sensor, with particular regards to pressure and temperature discrimination.
Keywords: fibre Bragg gratings; fibre segment interferometry; pressure sensing; interferometry; optical fiber sensors